Historyczne uwarunkowania rozwoju audytu wewnętrznego - Bednarek, Piotr (Historical factors of the development of internal auditing, 2009)
The paper presents the analysis of historical factors that influenced the emergence and evolution of internal audit profession. Thus general reasons for controlling employees are identified. Then the changes in definition, objectives and responsibilities of internal auditing are described. Finally contemporary events that have influence on the trends in practice of internal auditing are characterized. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, Nr 53, s. 9-19